Mercato: fatto o valore? Oltre la dicotomia - Rovelli, Riccardo (Market: fact or values? Beyond dichotomy!, 2008)
Economists are fond of proposing market solutions for many problems of resource allocation, while scholars from other social disciplines are often less inclined to adopt such solutions. In this essay I interpret the dichotomy for/against the market in the light of the one between neoclassical economics and the socio-anthropological tradition which originates with Karl Polanyi. In the first part, I suggest that this dichotomy runs in parallel to the one between facts and, which is typical of (neo)positivist thought. This dichotomy, which has been analyzed by Hilary Putnam, also reflects the self-portrait of neoclassical economics, as it has been proposed by Pareto and Robbins. Following this perspective in the second part I suggest on the one hand that the work of Polanyi should be interpreted as a reaction to neoclassical economics, but on the other hand it is also based on an incorrect interpretation of both facts and ideas in the history of ancient societies. Finally I notice that, although recent researches confirm that ancient societies should be interpreted as "conglomerations of interdependent markets" (thus following Temin against Polanyi and Finley), the presence and relevance of markets does not justify an under-socialized interpretation of ancient market economies: on the contrary, as it was well clear to many scholars, in a tradition that loosely connects Homer with Adam Smith, markets are and should be interpreted as value-laden facts. In the conclusion I discuss some implications of this view for the analysis of contemporary society.
Keywords: PUTNAM, Hilary, 1926-2016; SMITH, Adam, 1723-1790; economists; feasibility studies; markets - social aspects; neoclassical economics; neoclassical school of economics; resource allocation